The recovery experience Stress, recovery capital, and personal views on addiction and recovery in post-treatment addiction recovery. - Castillo, T. C.
The recovery experience is a research study that explores the experiences of individuals in post-treatment addiction recovery according to stress, recovery capital and personal views on addiction and recovery. Existing literature suggests that individuals with addiction require a substantial quality of recovery capital to overcome stress and challenges in all stages of recovery. In this research study, it focused on a specific stage in recovery, post-treatment addiction recovery, since there is a great need to explore what happens after treatment. The research adapted a case study research design and interviewed eight (8) participants on experiences in post-treatment addiction recovery. Interview responses were analyzed through categorizing codes and themes and submitting for external audit. Results showed that the recovery experience in post-treatment addiction recovery involves dealing with stress during reintegration to the mainstream environment and daily functioning (getting a job, earning money, fulfilling responsibilities). Recovery connections, social support and recovery-supportive activities were important factors in sustaining recovery. Addiction was considered as a lifestyle of powerlessness and loss of control over substances while recovery was depicted as an ongoing process requiring support and finding purpose in being in recovery.